The Authority of Religious Courts in Resolving Sharia Economic Disputes in Indonesia - Romel Tarigan (AT-TAFAHUM: Journal of Law, 2026)
The development of the sharia economy in Indonesia has increased the need for a dispute resolution system that is able to provide legal certainty in accordance with sharia principles. The expansion of the authority of the Religious Courts through amendments to the Religious Courts Law is an important foundation in resolving sharia economic disputes. This research aims to analyze the legal basis of the authority of the Religious Courts in resolving sharia economic disputes and to examine the effectiveness of the implementation of this authority in providing legal protection for the parties. The research uses normative legal research methods with a legislative approach and a conceptual approach. Legal materials are obtained through literature studies consisting of laws and regulations, books, scientific journals, and other literature related to sharia economics and Religious Courts. All legal materials are analyzed qualitatively using descriptive-analytical methods. The results of the study show that the authority of the Religious Court in resolving sharia economic disputes has provided legal certainty regarding the institution authorized to adjudicate disputes arising from transactions based on sharia principles. However, the effectiveness of its implementation is still influenced by the quality of human resources, the complexity of sharia economic transactions, and the need for institutional capacity building. Therefore, strengthening the competence of judges, optimizing mediation mechanisms, and improving coordination between institutions is an important step in increasing the effectiveness of resolving sharia economic disputes through the Religious Court. Thus, the Religious Court has a strategic role in supporting the development of the sharia economy and providing legal certainty for the community.